1990
DOI: 10.3109/02713689008999616
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced production of inflammatory mediators by cultured ciliary epithelial cells

Abstract: Systemic injection of bacterial endotoxin (Lipopolysaccharide, LPS) in experimental animals induces anterior uveitis without major pathological changes in other organs. The present study investigates the effect of LPS on production of inflammatory mediators in cultured bovine pigmented ciliary epithelial cells (CB-cells) by means of radioimmunoassays and bioassays. LPS was found to stimulate CB-cells to secrete prostaglandin E2 and prostacyclin (assayed as its stable metabolite 6-keto-prostaglandin F1a), but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Both PGI 2 and PGE 2 increased significantly in vascular endothelial cells in response to LPS or TNF-␣ (27), in ciliary epithelial cells in response to LPS (28), in gingival fibroblasts in response to IL-1 or TNF-␣ (29), and in myometrial cells in response to IL-1 or TNF-␣ (30). Similarly, PGI 2 and PGE 2 production by aortic endothelial cells was elevated in response to xenoreactive antibodies and complement (31).…”
Section: Discussionmentioning
confidence: 99%
“…Both PGI 2 and PGE 2 increased significantly in vascular endothelial cells in response to LPS or TNF-␣ (27), in ciliary epithelial cells in response to LPS (28), in gingival fibroblasts in response to IL-1 or TNF-␣ (29), and in myometrial cells in response to IL-1 or TNF-␣ (30). Similarly, PGI 2 and PGE 2 production by aortic endothelial cells was elevated in response to xenoreactive antibodies and complement (31).…”
Section: Discussionmentioning
confidence: 99%
“…Jackson et al and Jung et al reported that IL-1β induced the expression of VEGF mRNA and protein in rheumatoid synoviocytes [27] and human lung epithelial cells [28]. Soluble or membranebound forms of IL-1β were produced by several cell types within the eye, including Mueller cells, macrophages, and vascular endothelial cells [29,30]. In fact, high levels of locally-produced IL-1β and VEGF have been found in mouse retinas undergoing retinal degeneration [31], as well as in the vitreous humor of patients with proliferative diabetic retinopathy [16,32], suggesting that the inflammatory milieu might enhance VEGF production.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is responsible for the production of great amount of pro-inflammatory PGs at inflammatory sites in animals and human with inflammatory diseases [ 19 ]. ICB is one of the major sources of NO and PGE2 production as well as inflammatory cells and plays a key role in the pathogenesis of EIU [ 8 , 9 ]. Our results show that the luteolin attenuated the expression of iNOS and COX-2 in the ICB, suggesting that blocking the expression of iNOS and COX-2 is one of the anti-inflammatory mechanisms of luteolin.…”
Section: Discussionmentioning
confidence: 99%